Effects of Probiotics BaSC06 on Intestinal Digestion and Absorption, Antioxidant Capacity, Microbiota Composition, and Macrophage Polarization in Pigs for Fattening - Cao, Xuefang; Tang, Li; Zeng, Zihan; Wang, Baikui; Zhou, Yuanhao; Wang, Qi; Zou, Peng; Li, Weifen (Frontiers in Veterinary Science, 2020)
This study aimed to compare the effects of BaSC06 and antibiotics on growth, digestive functions, antioxidant capacity, macrophage polarization and intestinal microbiota of pigs for fattening. A total of 117 pigs for fattening with similar weight and genetic basis were divided into 3 groups: Anti group (containing 40g/t Kitasamycin in the diet), Anti+Ba group (containing 20g/t Kitasamycin and 0.5×108 CFU/kg BaSC06 in the diet) and Ba group (containing 1 108 cfu/Kg Ba in the diet without any antibiotics). Each treatment was performed in three replicates with 13 pigs per replicate. Results showed that BaSC06 replacement significantly improved the ADG (P<0.05), intestinal digestion and absorption function by increasing the activity of intestinal digestive enzymes and the expression of glucose transporters SGLT1 (P<0.05) and small peptide transporters PEPT1 (P<0.05). Besides, BaSC06 supplementation enhanced intestinal and body antioxidant capacity by activating the Nrf2/Keap1 antioxidant signaling pathway due to the increased expression of p-Nrf2 (P<0.05). Notably, BaSC06 alleviated intestinal inflammation by inhibiting the production of pro-inflammatory cytokines, IL-8, IL-6 and MCP1 (P<0.05), and simultaneously increasing the expression of M1 macrophage marker proteins iNOS (P<0.05) and M2 macrophage marker proteins Arg (P<0.05) in the intestinal mucosa. Moreover, BaSC06 promoted the polarization of macrophages to M2 phenotype by stimulating the STAT3 signaling pathway. It was also noted that BaSC06 improved the composition of the microbiota by enhancing the proportion of Firmicutes, and reducing that of Bacteroidetes and Proteobacteria. Taken together, our results indicate that supplementation of BaSC06 in the diet of pigs for fattening improves the growth, mucosal structure, antioxidative capacity, immune functions (including increasing M1and M2 polarization of macrophage) and composition of intestinal microbiota, which is much better than antibiotics, suggesting that it is an effective alternative to antibiotics in the preparation of pig feed.